Can blind persons accurately assess body size from the voice? - Pisanski, Katarzyna (Biol Lett, 2016)
Vocal tract resonances provide reliable information about a speaker's body size that human listeners use for biosocial judgements as well as speech recognition. Although humans can accurately assess men's relative body size from the voice alone, how this ability is acquired remains unknown. In this study, we test the prediction that accurate voice-based size estimation is possible without prior audiovisual experience linking low frequencies to large bodies. Ninety-one healthy congenitally or early blind, late blind and sighted adults (aged 20–65) participated in the study. On the basis of vowel sounds alone, participants assessed the relative body sizes of male pairs of varying heights. Accuracy of voice-based body size assessments significantly exceeded chance and did not differ among participants who were sighted, or congenitally blind or who had lost their sight later in life. Accuracy increased significantly with relative differences in physical height between men, suggesting that both blind and sighted participants used reliable vocal cues to size (i.e. vocal tract resonances). Our findings demonstrate that prior visual experience is not necessary for accurate body size estimation. This capacity, integral to both nonverbal communication and speech perception, may be present at birth or may generalize from broader cross-modal correspondences.